2013
DOI: 10.1118/1.4804053
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of convergent collimators for pixelated SPECT systems

Abstract: These results demonstrate the potential of this kind of optimal convergent collimators for the use in small field of view imaging applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…The collimator in SPECT is a crucial component of the imaging chain that controls the noise, resolution, and sensitivity of the final functional image. [ 1 2 3 4 5 6 7 8 ] Specialized collimators are used for a specific imaging task, for example the fan beam collimator for brain imaging,[ 9 ] cone beam collimator for posterior portion of the thalamus,[ 10 ] slit slat collimator for radionuclide imaging with high-energy gamma ray emission,[ 11 12 ] and parallel-hole collimators that routinely use in SPECT and planar imaging. The pinhole and multi-pinhole collimators used for research, preclinical study, small animal, and focal uptake nuclear medicine imaging.…”
Section: Introductionmentioning
confidence: 99%
“…The collimator in SPECT is a crucial component of the imaging chain that controls the noise, resolution, and sensitivity of the final functional image. [ 1 2 3 4 5 6 7 8 ] Specialized collimators are used for a specific imaging task, for example the fan beam collimator for brain imaging,[ 9 ] cone beam collimator for posterior portion of the thalamus,[ 10 ] slit slat collimator for radionuclide imaging with high-energy gamma ray emission,[ 11 12 ] and parallel-hole collimators that routinely use in SPECT and planar imaging. The pinhole and multi-pinhole collimators used for research, preclinical study, small animal, and focal uptake nuclear medicine imaging.…”
Section: Introductionmentioning
confidence: 99%
“…11,40 Different formulae apply to different hole shapes, 37,41 and it has also been shown that hole tapering provides improved sensitivity at equal resolution. 42,43 When the object of interest is relatively large, it may be appropriate to use diverging collimators, 44 e.g., for kinetic modeling in mice, it is important to see the organ of interest and the heart within a single bed position in order to obtain an arterial input curve. 45 Although diverging collimators have not been very common in the past, with the arrival of new high-resolution detector technologies, it becomes possible to enlarge the FOV and still obtain a sufficiently high resolution.…”
Section: A2 Converging and Diverging Hole Collimatorsmentioning
confidence: 99%
“…Another approach that results in more conventional fan-and cone-beam collimator designs is presented in Ref. 43. This is based on the same principle of local optimization but it assumes that the optimal collimator thickness and hole diameter are constant and equal to their values near the center of the collimator and that the focal point lies as close as possible behind the object, given the constraint that the FOV must contain the whole body/organ.…”
Section: A Sensitivity Maximization For a Given Target Resolutionmentioning
confidence: 99%
See 2 more Smart Citations